Electromagnetic-thermal Scale Model of Gas-Insulated Bus Bars - Hongtao Li; Naiqiu Shu; Ling Li; Hui Peng; Zipin Li (Institute of Advanced Engineering and Science, 2014)
Knowledge of the heat dissipation ability of gas-insulated bus bars (GIB) is paramount in the design stage. To reduce the capital cost, a scale model which has the identical electromagnetic-thermal characteristics of a full scale GIB is designed in this paper. The scaling relationships of the power losses, convection heat transfer, radiant heat transfer and thermal equilibrium are analyzed based on the governing equations and non-dimensional correlations. Current densities, power losses, convective heat transfer coefficients and temperature distributions in conductor and tank of the prototype and the scale models under different load currents are compared by FEM (Finite Element Method). The effectiveness of scale models is validated by the comparison between calculated and test results.